(3HGfJ SYGOs - (3cYH Hf RgjQ , CHh GdeZQH,J (B26 (3g` s
(3ChdgG (B:s
(3HGfJ SYGO abdHi Gdjhe eJHhd eJje EKQgG de jaO ecHhd s
(3BNQgG (B:s
(3dG jhbYhG GdWYf EdG ai fMhQge heGdge Yf MjGd GdehJ Jgdjd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B87 - (3U(B89s
(3GfXQgG eY QSGdI GdUGMH Hf YHGO ai cTa Yjhf GdeJfHis
(3fSNI KGdKIs
(3hQO CjVG JMJ Qbe (B2185(3, (B2187s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B226s
(3GdLRA (B2 - (3U (B1329 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B105 s
Keywords: (3GdCOHs